Improving Student Creativity Through Talking Stick Method in Indonesian Language Learning - Alviana Dwi Anggreni (Prosiding University Research Colloquium, 2021)
Bahasa Indonesia learning is a compulsory lesson taught from elementary school tocollege. the purpose of this research is to find out how the influence of talking stickmethod in improving the creativity of Indonesian language learning. The method in thestudy was to use class actions on students' creativity by using talking stick method. Theobject of this study was a grade 2 student at SD Jambewangi who numbered 25 students.The results showed that the application of talking stick learning model is able to improvethe learning of Bahasa Indonesia, this can be seen in the table of student's practicalityresearch results. The method in the study was to use class actions on students' creativityby using talking stick methods. The object of this study was a grade 2 student at SDJambewangi who numbered 25 students. The results showed that the application oftalking stick learning model is able to improve the learning of Bahasa Indonesia, this canbe seen in the table of student's practicality research results. The conclusion of this studyis that talking stick learning method makes students more understanding in answeringquestions given in Bahasa Indonesia material. Therefore, with the application of talkingstick learning methods can be developed to improve the learning process in the classroomand student learning outcomes.